The impact of the centralisation of workplaces and business entities on spatial development - Čok, Gregor (Geodetski vestnik, 2021)
The paper presents the results of a study to define the current size and location of workplaces and business entities in the area. The research was conducted in three stages. In the first step, the analysis of the size and distribution of workplaces according to the municipalities in the Republic of Slovenia for the 2007-2019 period was carried out. In the second step, the size and distribution of business entities in the space were examined. In the third step, a more detailed analysis was carried out in the test area of the Osrednjeslovenska statistical region, based on: the location in Ljubljana Urban Municipality (hereinafter referred to as MOL), in the municipalities directly bordering MOL and in the other municipalities of the Osrednjeslovenska statistical region. At this stage we also focused on the sector of activity of business entities. A strong upward trend in workplaces was found in only a few major urban centres along the motorway junction, especially in MOL. The same applies to the concentration of business entities. All this suggests that the existing practice of planning activities in physical space does not follow the strategic orientations of spatial acts, which could better control the spatial processes and their consequences.
Keywords: business entities; centralisation; centralizacija; delovna mesta; land use; Osrednjeslovenska statistical region; osrednjeslovenska statistična regija; poslovni subjekti; prostorski razvoj; raba prostora; Slovenia; Slovenija; spatial development; workplaces